Ultrasonographic and classical risk factors of carotid atherosclerosis in patients with type-2 diabetes mellitus - Šantl-Letonja, Marija (Acta medico-biotechnica, 2013)
Purpose: We determined the prevalence of the clinical and biochemical risk factors as well as the extent of atherosclerosis in carotid arteries in patients with diabetes mellitus type 2(DMT2). Methods: A total of 289 subjects with DMT2 and 157 healthy subjects were enrolled in this prospective cross-sectional study. Leveles of total cholesterol, high-density lipoprotein-cholesterol (HDL-C), low-density lipoprotein-cholesterol (LDL-C), triglycerides, fasting, blood glucose, fribrinogen, and high-sensitivity C-reactive protein (hsCRP) were measured using standard biochemical methods. Carotid atherosclerosis was assessed by ultrasonography. Intima media thickness (IMT), plaque type and plaque score were also determined.
Keywords: carotid atherosclerosis; diabetes mellitus; karotidna ateroskleroza; markers of atherosclerosis; metabolni sindrom; sladkorna bolezen